2016
DOI: 10.5114/ada.2016.62839
|View full text |Cite
|
Sign up to set email alerts
|

Can pregnancy-associated plasma protein-A be a marker for the assessment of atherosclerosis risk in patients with chronic plaque psoriasis?

Abstract: IntroductionPsoriasis is an immune-mediated chronic inflammatory dermatosis. Several studies have shown that patients with psoriasis have a much greater risk of cardiovascular diseases than the normal population. The chronic inflammation observed in psoriasis is thought to have a role in the development of atherosclerosis and vascular endothelial injury.AimTo examine serum pregnancy-associated plasma protein-A (PAPP-A) levels, which has been regarded as a marker of early stage atherosclerosis in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In psoriasis, the top markers correlating with severity included corticotropin‐releasing hormone and pregnancy‐associated plasma protein A, markers of early‐stage atherosclerosis, 54,55 previously reported in patients with psoriasis ( r > 0·7; P < 0·05) 54,56,57 . Other markers positively correlated with psoriasis severity included CD69 (a T‐cell marker and a key mediator of psoriasis pathogenesis), 58 granzyme B (a natural killer/T‐cell marker related to atherosclerosis), 59 IL‐17A, IL‐17F, IL‐19 (Th17‐related), CCL23 and CCL13 (Th2‐related), the dendritic cell marker CD300E and IL‐1α (suggested to link immune activation and atherosclerosis) ( r ≥ 0·55; P ≤ 0·1) 38,60,61 …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In psoriasis, the top markers correlating with severity included corticotropin‐releasing hormone and pregnancy‐associated plasma protein A, markers of early‐stage atherosclerosis, 54,55 previously reported in patients with psoriasis ( r > 0·7; P < 0·05) 54,56,57 . Other markers positively correlated with psoriasis severity included CD69 (a T‐cell marker and a key mediator of psoriasis pathogenesis), 58 granzyme B (a natural killer/T‐cell marker related to atherosclerosis), 59 IL‐17A, IL‐17F, IL‐19 (Th17‐related), CCL23 and CCL13 (Th2‐related), the dendritic cell marker CD300E and IL‐1α (suggested to link immune activation and atherosclerosis) ( r ≥ 0·55; P ≤ 0·1) 38,60,61 …”
Section: Resultsmentioning
confidence: 94%
“…In psoriasis, the top markers correlating with severity included corticotropin-releasing hormone and pregnancy-associated plasma protein A, markers of early-stage atherosclerosis, 54,55 previously reported in patients with psoriasis (r > 0Á7; P < 0Á05). 54,56,57 Other markers positively correlated with psoriasis severity included CD69 (a T-cell marker and a key mediator of psoriasis pathogenesis), 58 granzyme B (a natural killer/T-cell marker related to atherosclerosis), 59 IL-17A, IL-17F, IL-19 (Th17-related), CCL23 and CCL13 (Th2-related), the dendritic cell marker CD300E and IL-1a (suggested to link immune activation and atherosclerosis) (r ≥ 0Á55; P ≤ 0Á1). 38,60,61 Top proteins positively correlated with HS clinical severity included tissue growth factor-related markers [such as growth hormone 1, chordin like 2 and transforming growth factor (TGF)-a], along with markers related to increased cardiovascular risk [PLA2G2A, CHI3L1 and matrix metalloproteinase (MMP)9], TNF, key Th1-related chemokines (CXCL9/ CXCL10) and Th17-and Th2-related receptors (IL-17RA and IL-4R) (r > 0Á7; P < 0Á01).…”
Section: Immune and Cardiovascular Biomarkers Correlate With Psoriasi...mentioning
confidence: 90%
“…found that PAPP-A levels were high in psoriasis patients, and they also found that PAPP-A levels correlated with the duration and severity of the disease. They suggested that high PAPP-A levels were related with atherosclerosis, and the use of PAPP-A as a screening test for cardiovascular risk assessment should be supported by further studies [ 24 ]. Unlike that study, we found no significant difference in moderate-severe psoriasis patients compared to the control group in terms of PAPP-A levels as hs-CRP levels, which is an important marker for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%